Novel Compact Multiband MIMO Antenna for Mobile Terminal - Cheng Yang; Yuan Yao; Junsheng Yu; Xiaodong Chen (International Journal of Antennas and Propagation)
A novel compact MIMO antenna for personal digital assistant (PDA) and pad computer is proposed. The proposed antenna is composed by two multipatch monopole antennas which are placed 90° apart for orthogonal radiation. To strengthen the isolation, a T-shaped ground branch with proper dimension is used to generate an additional coupling path to lower the mutual coupling (below −15 dB), especially at GSM850/900 band. The proposed MIMO antenna is fabricated and tested, both the simulated and the measured results are presented, and some parametric studies are also demonstrated. In addition, there are some advantages about the proposed antenna such as simple structure, easy fabrication, and low cost.